Publishing Beyond Print - ,V. K, Bharti; M. P, Singh; Bharti, Sanjay; -, Sandeep; -, Meetali; -, Deepshikha (International Journal of Information Studies, 2025)
With the advent of Information and Communication Technologies, the trend in collecting, acquiring, storing, retrieving and disseminating materials and documents has changed. E-Publishing has gained momentum in the present era. It has become the ideal form for disseminating the latest research findings and results. It is basically a form of publishing in which books, journals, and other materials are being produced and stored electronically rather than in print. E-Publishing includes the digital publication of e-books, electronic articles and the development of digital libraries and catalogues. This paper provides recent e-publishing trends and overview of e-publishing in India.